Kesadaran Hukum Pelaku Usaha Terhadap Larangan Bai’ Najasy Pada Praktik Fake Order - Rini, Ashri Puspita; Jumailah, Jumailah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study examines fake orders, which are fictitious orders. In Islam, fake orders are included in the Bai’ Najasy category, which is market manipulation that is prohibited because it contains elements of fraud and injustice. To improve the reputation of the store, some business actors in e-commerce transactions make fake orders. Therefore, awareness of Islamic law is an important factor in preventing this practice in order to comply with the principles of honest and transparent transactions. This study uses a qualitative approach with a case study method on e-commerce business actors in Pekalongan. The results of the study show that the level of awareness of Islamic law among business actors is still low. Most business actors do not understand the concept of Bai’ Najasy in depth and are not aware that fake orders are included in practices that are prohibited in Islam. This practice is generally carried out with the aim of increasing customer trust and business competitiveness without considering its legal impact. Awareness of Islamic law in e-commerce transactions still needs to be improved through education and socialization. The government, academics, and e-commerce platforms need to work together in providing understanding to business actors so that they are more compliant with sharia principles. Stricter regulations are also needed to suppress the practice of Bai’ Najasy in transactions.